An Outbreak of Severe Acute Respiratory Syndrome-2019 (COVID-19): A Major Health Concern - Sajad, Mohd; Ahmed, Mofieed; Thakur, Sonu Chand (Indian Journal of Pharmaceutical Education and Research, 2020)
In Wuhan City, the province of Hubei, China, there appeared an unusual epidemic of pneumonia of uncertain ethology in December 2019. A novel coronavirus was identified by the World Health Organisation (WHO) as the triggering agent and subsequently named COVID-19. Considered a relative of SARS, which infected the lower respiratory tract and manifested in people as pneumonia, COVID-19 is the product of a beta-Corona virus called SARS-COV-2. The frequency of COVID-19 infection continue to increase, with more than 278,467 deaths worldwide till May 9, 2020. To stop their further spread scientists and researchers are racing to investigate the nature of this virus and their effects. We summarize the current state of knowledge around COVID-19and the role of some dietary vitamins and immune enhancers that may help the immune system in fight against COVID-19. Moreover, it also highlights the impact of COVID-19 lockdown on pollution particularly in India, in response to this global outbreak.
Keywords: COVID-19; Pandemic; Outbreak; Lockdown; Pollution; Nutrition